“The Testament” of XII Pandito Hambo-Lama Dashidorzhi Ithegelov in the Context of Buddhist Philosophy - Elizaveta E. Baldanmaksarova (Studia Litterarum)
The article deals with a hitherto unexamined literary text written by a famous Buddhist philosopher and scientist XII Pandito Hambo-Lama Dashidorzhi Itigelov. This text is the last poem by D. Itigelov entitled “The Testament” (1927) written in the genre of the epistle and addressed to the people of the 21 st century. 2017 is a year of the 90th anniversary of the phenomenal state achieved by the philosopher; on September 10, Buryat people celebrate the 15th anniversary of his acquisition of the Precious Inexhaustible Body. Not only was D. Itigelov a leader of the Buryat society who headed its religious and secular (state) activity until 1917, he also was an educated theologian and a gifted writer who left rich literary, religious, and philosophical heritage relevant in the context of the Buddhist aesthetics and philosophy. This essay calls for the necessity to make this heritage available to public by stressing its originality and relevance for contemporary society.